ANALISIS EMPIRIK PENGGUNAAN INTERNET BANKING DAN MOBILE PHONE BANKING PADA BANK SYARIAH DAN KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) PADA MASA PANDEMI COVID-19 - Rahmayani, Fitri Ali; Thantawi, Tubagus Rifqy; Anwar, Miftakhul (SAHID BANKING JOURNAL, 2023)
Technological developments that occur continuously affect service patterns in the banking word. Islamic bank and KSPPS in charge of collecting funds and redistributing them as well as serving various other banking transactions can now be done digitally through internet banking and mobile phone banking services. The trend of using internet banking and mobile phone banking services certainly helps the community in conducting transactions during the Covid-19 pandemic. Through this research, it is expected to be able to identify the factors that influence the use of internet banking and mobile phone banking during the Covid-19 pandemic. There are 7 factors studied, namely comfort and safety, literacy, design and features, cost, environment, circumstances/conditions and benefits. The sample was obtained from 15 villages in the Cibungbulang sub-district with 85 respondents. The data analysis method used in this study is the confirmatory factor analysis (CFA) method which was tested using SPSS. It is hoped that this research can be used as an additional reference for future research.